Testing the tunnel effect: Comparison, age and happiness in UK and German panels - Felix R. FitzRoy; Michael A. Nolan; Max F. Steinhardt; David Ulph (IZA Journal of European Labor Studies, 2014)
In contrast to previous results combining all ages, we find positive effects of comparison income on happiness for the under 45s and negative effects for those over 45. In the UK, these coefficients are several times the magnitude of own income effects. In West Germany, they cancel out to give no effect of comparison income on life satisfaction in the whole sample when controlling for fixed effects, time-in-panel, and age-groupings. Pooled OLS estimation gives the usual negative comparison effect in the whole sample for both West Germany and the UK. The residual age-happiness relationship is hump-shaped in all three countries. Results are consistent with a simple life cycle model of relative income under uncertainty.
Keywords: D10; I31; J10; 330; Subjective life-satisfaction; Comparison income; Reference groups; Age; Welfare